2020
DOI: 10.3390/ijerph17144978
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dietary Supplements on the Bioaccessibility of Se, Zn and Cd in Rice: Preliminary Observations from In Vitro Gastrointestinal Simulation Tests

Abstract: Trace elements such as selenium (Se) and zinc (Zn) are essential elements in the human body, while cadmium (Cd) has no physiological function. A high proportion of people consume dietary supplements to enhance the performance of the body or alter the nutrient contents within the body. Therefore, this study was conducted to evaluate the interaction effects of several popular dietary supplements on the bioaccessibility of Se, Zn and Cd in rice with the hope of identifying dietary supplements that can increase ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 45 publications
(49 reference statements)
0
2
0
Order By: Relevance
“…Zn bioaccessibility refers to the fraction of soluble Zn in the digestion that was released from the rice grain. Zn bioaccessibility has been shown to be affected by Zn speciation, the digestion phase and various dietary components (Zhang et al 2020). The higher amount of bioaccessible Zn in progenies with high Zn density indicated that total Zn content had a positive effect on Zn bioaccessibility (Table 4).…”
Section: Discussionmentioning
confidence: 99%
“…Zn bioaccessibility refers to the fraction of soluble Zn in the digestion that was released from the rice grain. Zn bioaccessibility has been shown to be affected by Zn speciation, the digestion phase and various dietary components (Zhang et al 2020). The higher amount of bioaccessible Zn in progenies with high Zn density indicated that total Zn content had a positive effect on Zn bioaccessibility (Table 4).…”
Section: Discussionmentioning
confidence: 99%
“…43 The thiol group of Cys is a preferential metal-binding site considered to be largely implicated in its complexation with metals. 30 Zhang et al 45 reported that the addition of Met increased Cd bioaccessibility in rice in the intestinal phase. Vadas and Ahne 46 found that Cys could effectively solubilize Cd and Pb from contaminated soils because of its ability to form stable complexes with metals through its thiol ligand.…”
Section: Concentrations Of Met and Cys In Wheatmentioning
confidence: 99%